Phosphatidylinositol-3′-kinase/AKT signaling is essential in synovial sarcoma - Friedrichs, Nicolaus; Trautmann, Marcel; Endl, Elmar; Sievers, Elisabeth; Kindler, Dagmar; Wurst, Peter; Czerwitzki, Jacqueline; Steiner, Susanne; Renner, Marcus; Penzel, Roland; Koch, Arend; Larsson, Olle; et al. (International journal of cancer, 2011)
Synovial sarcomas account for 5-10% of all malignant soft tissue tumors. They have been shown to express different membranous growth factor receptors, many of them signaling via intracellular kinase cascades. In our study, the functional role of PI3K/AKT signals in synovial sarcoma is analyzed with regard to tumor biology and therapeutic applicability. Immunohistochemical stainings of (Ser473)-phosphorylated (p)-AKT, its targets p-(Ser9)-GSK-3β and p-(Ser2448)-mTOR and the cell cycle regulators Cyclin D1 and p27KIP1 were performed in 36 synovial sarcomas. The PIK3CA gene was screened for mutations. In vitro, four synovial sarcoma cell lines were treated with the PI3K inhibitor LY294002. Phosphorylation of AKT, GSK-3β and mTOR was assessed, and cellular proliferation and apoptosis were analyzed to functionally characterize the effects of PI3K inhibition. Finally, coincubations of LY294002 with cytotoxic drugs were performed. Most tumors showed significant expression levels of p-AKT, p-GSK-3β and p-mTOR, indicating activation of the PI3K/AKT signaling cascade in synovial sarcomas; Cyclin D1 and p27KIP1 were differentially expressed. Mutations in the PIK3CA gene could be excluded. In vitro, PI3K inhibition diminished synovial sarcoma cell growth accompanied by reduced phosphorylation of AKT, GSK-3β and mTOR. Mechanistically, PI3K pathway inhibition lead to enhanced apoptosis and decreased cellular proliferation linked to reduced Cyclin D1 and increased p27KIP1 levels. Simultaneous treatment of synovial sarcoma cell lines with LY294002 and cytotoxic drugs resulted in additive effects. In summary, PI3K signaling plays an essential role in growth control of synovial sarcomas and might be successfully targeted in multimodal therapeutic strategies.
Gesehen am 26.04.2023
Erste Veröffentlichung: 02. Dezember 2010